Phase Transfer of Mo2C Induced by Boron Doping to Boost Nitrogen Reduction Reaction Catalytic Activity. (9th February 2022) - Fan, Binbin; Wang, Haozhi; Zhang, Hong; Song, Yue; Zheng, Xuerong; Li, Changjiu; Tan, Yeqiang; Han, Xiaopeng; Deng, Yida; Hu, Wenbin
Abstract: Facilitating the cleavage of a NN bond and suppressing the competition hydrogen evolution reaction is essential, and but still remains a challenge in nitrogen reduction reaction (NRR). Crystal phase tailoring is an effective approach to optimize the energy barrier during the NRR process to improve the catalytic efficiency. Herein, a boron‐doping strategy to induce phase transfer from hexagonal Mo2 C to cubic Mo2 C for regulating the electronic structure and catalytic properties of electrocatalysts toward NRR is reported. The B doped cubic Mo2 C is found to increase the exposure of active sites, regulate the d band center of Mo for enhancing the adsorption and activation of nitrogen, and reduce the energy barrier of NRR pathway, giving rise to a high ammonia yield of 52.1 μg h −1 mg −1 at −0.6 V versus reversible hydrogen electrode under ambient conditions. More importantly, the hydrogen adsorption on the surface of electrocatalyst is significantly inhibited due to the B‐doping, further improving the faradic efficiency to 36.9%, which is 4 times that of hexagonal Mo2 C (9%). This work not only sheds light on the atomic‐scale design of efficient NRR electrocatalysts, but also provides a promising avenue for synchronizing the catalytic activity and selectivity for catalytic reactions. Abstract : A boron‐doping strategy is employed to fabricate the boron doped Mo2 C electrocatalyst (B‐Mo2 C) with a cubic structure for nitrogen reduction reaction. The nitrogen adsorption on cubic B‐Mo2 C is effectively enhanced by tailoring the crystal and electronic structure. More importantly, the competing hydrogen evolution reaction on the catalyst is significantly suppressed, leading to a four‐fold improved faradic efficiency.